Preparation and Optimization of In Situ Gel Loaded with Rosuvastatin-Ellagic Acid Nanotransfersomes to Enhance the Anti-Proliferative Activity - Khaled M. Hosny; Waleed Y. Rizg; Rasha A. Khallaf (Pharmaceutics, 2020)
The objective of this study was to develop an optimized sustained-release nanotransfersomes (NTS) based in situ gel formulation of rosuvastatin (RO) combined with ellagic acid (EA) antioxidant, to enhance cytotoxic and anti-proliferative activity against tongue carcinoma. The concentrations of lecithin, Tween 80, and d-tocopherol polyethylene glycol succinate (TPGS) were considered as independent variables. Particle size, entrapment, and stability were selected as dependent variables. The obtained formulation containing 25% lecithin, 20% Tween 80, and TPGS 15% fulfilled the prerequisites of the optimum formulation. RO-NTS loaded in situ gel was prepared and optimized for concentrations of Poloxamer 407, and Carbopol, using statistical design. Drug release from in situ gel showed a sustained release profile. The RO IC50 was decreased by half for the in situ gel in comparison to plain RO and RO-EA-NTS. A significant amount of caspase-3 was detected in all the formulation treatments. The studies indicated that EA’s synergistic anti-oxidant effect owing to a high affinity to the PGP efflux transporter and higher penetration in the RO-NTS formulation led to a higher inhibition against human chondrosarcome-3 cancer cell lines. RO-EA NTS−loaded in situ gel had a sustained release that could be significant in localized therapy as an alternative to surgery in the treatment of aggressive tongue carcinoma.